Desenhos geométricos: métodos construtivos no ensino de geometria euclidiana - Silva, Tiago Reis (2024)
The main focus of this dissertation is the use of construction methods, exploring teaching methods that facilitate the understanding of geometric concepts by students. Using construction techniques with ruler and compass, which go beyond the simple use of formulas and calculations, proposing a practical and visual approach, where students are encouraged to construct geometric elements using the tools and realizing the relationships between the different elements in the figures that are building. Furthermore, it discusses the importance of integrating these constructive techniques into the school curriculum, highlighting the benefits of more active and engaging learning. The approach aims to support teachers and educators so that they can apply these concepts and improve student performance in geometry, seeking to increase student interest and engagement in the study of this topic.